Disablement and care: a comparison of patient views and general practitioner knowledge - Patrick, D. L. (1982)
A questionnaire was used to assess general practitioners' knowledge of handicaps and service use among disabled patients in a group practice. The disabled patients were identified by a postal screening questionnaire. Sixty-eight were subsequently interviewed to assess the severity of restrictions on their activities and to collect information about informal support and use of community or hospital services. The areas of life in which the disabled were most affected by their medical conditions were sleep and rest, household management, emotion and mood. Relatives assisted the disabled considerably with all daily activities but more help was requested. Most disabled patients had consulted their general practitioner or attended casualty and outpatient clinics, but only a minority had used other community services. Prescription of drugs was considered the most important service the doctor provided. A second questionnaire, which the general practitioners completed with the help of their records, revealed that they knew of only 50 per cent of the difficulties with daily living reported by the disabled and even less of the aids, appliances and services used. A better awareness of these facilities among general practitioners might lead to a more effective distribution of resources among their patients.